Human Salivary Protein Histatin 5 Has Potent Bactericidal Activity against ESKAPE Pathogens - Du, Han; Puri, Sumant; McCall, Andrew; Norris, Hannah L.; Russo, Thomas; Edgerton, Mira (Frontiers in Cellular and Infection Microbiology, 2017)
ESKAPE (Enterococcus faecium, Staphylococcus aureus, Klebsiella pneumoniae, Acinetobacter baumanni, Pseudomonas aeruginosa, and Enterobacter species) pathogens have characteristic multiple-drug resistance and cause an increasing number of nosocomial infections worldwide. Peptide-based therapeutics to treat ESKAPE infections might be an alternative to conventional antibiotics. Histatin 5 (Hst 5) is a salivary cationic histidine-rich peptide produced only in humans and higher primates. It has high antifungal activity against Candida albicans through an energy-dependent, non-lytic process; but its bactericidal effects are less known. We found Hst 5 has bactericidal activity against S. aureus (60–70% killing) and A. baumannii (85–90% killing) in 10 and 100 mM sodium phosphate buffer (NaPB), while killing of >99% of P. aeruginosa, 60–80% E. cloacae and 20–60% of E. faecium was found in 10 mM NaPB. Hst 5 killed 60% of biofilm cells of P. aeruginosa, but had reduced activity against biofilms of S. aureus and A. baumannii. Hst 5 killed 20% of K. pneumonia biofilm cells but not planktonic cells. Binding and uptake studies using FITC-labeled Hst 5 showed E. faecium and E. cloacae killing required Hst 5 internalization and was energy dependent, while bactericidal activity was rapid against P. aeruginosa and A. baumannii suggesting membrane disruption. Hst 5-mediated killing of S. aureus was both non-lytic and energy independent. Additionally, we found that spermidine conjugated Hst 5 (Hst5-Spd) had improved killing activity against E. faecium, E. cloacae, and A. baumannii. Hst 5 or its derivative has antibacterial activity against five out of six ESKAPE pathogens and may be an alternative treatment for these infections.